(untitled) (Tanzania Medical Journal, 2020)
Background Breast cancer is the second most common cancer among Tanzanian women. Advanced disease at presentation is not uncommon among our patients with reasons for such late presentation being unknown. Late presentation is costly to treat compared to early disease presentation, and further carries dismal outcome. Understanding factors related to late presentation will help formulate strategies to downstage the disease through early intervention. This study therefore sought to understand the factors related with late presentation among patients presenting with advanced breast cancer in Tanzania. Methodology This was an analytical cross-sectional hospital-based study that involved patients with advanced breast cancer at Muhimbili National Hospital during the period of study from February 2018 to January 2019. Delay was considered as presenting beyond three months following suspicion of breast mass. Socio-demographic variables and clinical presentation times at various facilities were determined. Descriptive and comparative statistics were computed. Results A total of 185 patients with a mean age of 48.4 years were involved in the study. Delay in seeking medical attention was noted in 76% of the patients with advanced breast cancer with young age, rural residency and lack of formal education showing significant association with delay in presentation. A mean of 125.7 days was spent before finally arriving for definitive care at Muhimbili National Hospital. Conclusion This study has recognized existence of late presentation following detection of breast mass among patients with advanced breast cancer in Tanzania. Studies to address delay among breast cancer patients are needed given the anticipated cost effectiveness. Key words: Delay, Advanced Breast Cancer, Stage 3 and 4, Breast, Late Presentation.